Identification of novel components of the retinal determination gene network in Drosophila cell lines - Robert A. Drewell; Jacqueline M. Dresch (Open Biology)
The retinal determination genetic network controls the development of the visual system in all seeing animals through the molecular regulation of cells to adopt an eye tissue fate. The compound eye of the fruit fly, Drosophila melanogaster, is an excellent model system to study the complex mechanisms within the network that regulate specification of cellular identity during embryogenesis. In Drosophila, the two Pax6 paralogues, eyeless and twin of eyeless, sit at the very pinnacle of the network and their expression early in development activates critical downstream components of the retinal determination pathway. In this study, we investigate the expression of 21 known components of the network in two established embryonic cell lines, Kc167 and S2 cells, that show reciprocal expression patterns for the two Pax6 paralogues. Network mapping reveals that many of the components of the network demonstrate extensive interactions with additional factors. Integrating the transcriptional profile of the cell lines, interaction maps and embryonic expression patterns enables us to identify 16 potential novel components of the genetic network, 11 of which are transcription factors. We confirm the regulatory potential for a subset of the novel transcription factors through the identification of predicted binding sites in previously characterized enhancers for the core genes in the network.